A Cultural Orientation Approach to Work Orientation: Mongolian Workers' Jobs, Careers, and Callings. (December 2022) - Park, Jiyoung; Choi, Yeeun; Chao, Melody M.; Beejinkhuu, Uurtsaikh; Sohn, Young Woo
Culturally held beliefs about the self and its relations with others affect the way individuals view their work. In this study, we examined the associations between individualism-collectivism and the three work orientations (i.e., viewing work as a job, a career, or a calling). We also investigated whether the positive effects of a calling orientation can be generalized to a developing eastern country, Mongolia. Using a sample of 352 Mongolian workers, we found that those endorsing horizontal collectivism tended to view their work as a calling more than as a job or a career. Mongolians with a calling orientation reported having better satisfaction with job, salary, and life, more work meaningfulness, and less turnover intention than those viewing work as a job or a career. The results suggest that cultural orientations and work orientations are intertwined, and the positive roles of a calling orientation are generalizable to Mongolia.